2021
DOI: 10.1186/s40168-021-01073-2
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome and mosquito vectorial capacity: rich potential for discovery and translation

Abstract: Microbiome research has gained considerable interest due to the emerging evidence of its impact on human and animal health. As in other animals, the gut-associated microbiota of mosquitoes affect host fitness and other phenotypes. It is now well established that microbes can alter pathogen transmission in mosquitoes, either positively or negatively, and avenues are being explored to exploit microbes for vector control. However, less attention has been paid to how microbiota affect phenotypes that impact vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 166 publications
2
73
0
Order By: Relevance
“…Several distinct microbial-based approaches are currently being investigated [ 9 11 ]. However, it is unclear whether these approaches are compatible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several distinct microbial-based approaches are currently being investigated [ 9 11 ]. However, it is unclear whether these approaches are compatible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pursuit of novel, eco-friendly alternative tools is urgently needed to complement traditional malaria control strategies. In particular, the development of endosymbiont-based control strategies is receiving increasing attention, as microbes have desirable properties for vector control [ 9 11 ]. One approach, known as paratransgenesis, aims to inhibit the development of the parasites or to interfere with their competence and fitness by expressing effector molecules from symbiotic bacteria [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The blood meal is required for the maturation of eggs but at the same time, the mosquito spreads pathogens to humans through which the disease is transmitted and maintained. As a result, host selection and blood-feeding behavior are critical, as a higher biting rate leads to an increased vectorial capacity as the vector has more opportunity to infect and transmit pathogens [4]. Recently, it was observed that the source of the mosquito blood meal has a strong influence on vector microbiota [25,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes' blood-feeding habit not only provides them with critical blood proteins and nutrients for egg production and reproductive fitness, but it also allows pathogens to establish themselves in and be transmitted to humans by their arthropod hosts [2,3]. Therefore, both blood-feeding behavior and blood meal host preference are critical as an increased biting rate leads to an increased vectorial capacity wherein the vector has more chances to acquire and spread pathogens [4]. However, studies have revealed that the blood quality, and thus host species, can alter reproductive output, suggesting that disease vectors have a specialized blood-feeding behavior [5].…”
Section: Introductionmentioning
confidence: 99%
“…A similar pattern was evident for the abundance of Flavobacteriaceae, which was higher in both +/+ and +/-compared to -/-mosquitoes (Mann-Whitney, p<0.001, p<0.01 respectively). The increased bacterial load may also be associated with the reduced lifespan of the Aper1-Sco GM mosquitoes (27).…”
Section: Scorpine Expression In the Aper1 Locus Affects The Mosquito Gut Microbiotamentioning
confidence: 99%